Corporate Governance Ratings of Indonesia State-Owned Enterprise on Firm Performance 2012-2016 - Nugraha, Aditya (2017)
The study investigates the association of Corporate Governance Rating on the firm’s performance. Based on a sample of 58 State owned Enterprise of Indonesia, the findings from the study confirm there are no relationship between corporate governance rating and firm’s performance. The study contributes to the corporate governance discipline with additional empirical evidence of the impact of corporate governance rating on the firm’s performance, especially in emerging countries.